Clinico-Microbiological Profile and Treatment Outcome of Infectious Scleritis: Experience from a Tertiary Eye Care Center of India - Srikant Kumar Sahu; Sujata Das; Savitri Sharma; Kalyani Sahu (International Journal of Inflammation)
Medical and microbiology records of seventeen patients (17 eyes), diagnosed as scleritis of infectious origin were reviewed; to study clinical features, predisposing risk factors, microbiologic profile and treatment outcome of infectious scleritis. The mean patient age was 52.3±19.75 years. Twelve patients (70.6%) had history of trauma/prior surgery. Isolated organisms included Staphylococcus species (spp) (n=5), Fungus (n=4), Nocardia spp (n=3), two each of atypical Mycobacterium spp and Streptococcus pneumoniae and one Pseudomonas aeruginosa. Treatment included intensive topical antimicrobial in all eyes and systemic medication in 15 (88.2%) patients; surgical exploration was needed for 13 (76.5%) patients and scleral patch graft was done in four (23.5%) patients. Lesions resolved in all patients and none required evisceration. The presenting log MAR visual acuity of 1.77±1.40 and improved to 0.99±0.91. (P≤0.039) after treatment with a mean follow up of 22.57±19.53 weeks. A microbiological confirmation, appropriate medical and/or surgical intervention has a good tectonic and visual outcome.